Coupled treatment of lignocellulosic agricultural residues for augmented biomethanation. (10th March 2019) - Yadav, Monika; Paritosh, Kunwar; Pareek, Nidhi; Vivekanand, Vivekanand
Abstract: Naturally abundant, non-edible and inexpensive lignocellulosic biomass is an appropriate substrate for biogas production through anaerobic digestion. In order to attain most of the hydrolyzable sugars, a pretreatment phase is required before subjecting the biomass to anaerobic digestion. In this regard, lignin-degrading fungi provide an environment-friendly, clean and energy efficient process as compared to physical and chemical pretreatment methods. In the present study, biological pretreatment of pearl millet and wheat straw was carried out by employing lignolytic fungus Pleurotus ostreatus to evaluate its efficiency for making these substrates easily degradable for enhanced biogas production. Characterization of untreated and pretreated biomass was performed by employing scanning electron microscopy, Fourier transform infrared spectroscopy and thermogravimetric analysis. Maximum increase of 101 and 71% in released reducing sugars was obtained after 42 days of pretreatment for wheat and pearl millet straw, respectively. Furthermore, biogas production potential of straw (wheat and pearl millet) subjected to one stage (fungal pretreatment only) and two-stage pretreatment (fungal pretreatment and bioaugmentation with chitinolytic bacterium Bacillus subtilis after 21 days) was evaluated to improve the process. Results revealed 46 and 51% increase in methane yield following two-stage pretreatment for wheat and pearl millet straw, respectively which were higher than the methane yield obtained after fungal pretreatment alone.